1993
DOI: 10.1111/j.1399-3054.1993.tb02511.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activation of plasma membrane H+– ATPase in Arabidopsis thaliana cells by turgor decrease and by fusicoccin

Abstract: The regulation of the H+‐ATPase of plasma membrane is a crucial point in the integration of transport processes at this membrane. In this work the regulation of H+‐ATPase activity induced by changes in turgor pressure was investigated and compared with the stimulating effect of fusicoccin (FC). The exposure of cultured cells of Arabidopsis thaliana L. (ecotype Landsberg 310–14‐2) to media containing mannitol (0. 15 or 0. 3 M) or polyethylene glycol 6000 (PEG) (15. 6% or 22% w/v) resulted in a decrease in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In other experimental systems such as bean (Vicia faba L.), hyperosmotic stress induced by mannitol treatment, caused a significant increase in the K and Cl uptake into leaf mesophyll cells (Shabala et al, 2000), providing an adequate osmotic adjustment. Moreover, in Arabidopsis similar results, increase in K uptake into cultured cells in response to hyperosmotic treatment (Curti et al, 1993) and decrease on Cl efflux induced by mannitol (Teodoro et al, 1998), were showed. In the present investigation, the data indicated a high negative correlation between soil moisture and build up of Na, K and Cl (Table 3).…”
Section: Discussionmentioning
confidence: 71%
“…In other experimental systems such as bean (Vicia faba L.), hyperosmotic stress induced by mannitol treatment, caused a significant increase in the K and Cl uptake into leaf mesophyll cells (Shabala et al, 2000), providing an adequate osmotic adjustment. Moreover, in Arabidopsis similar results, increase in K uptake into cultured cells in response to hyperosmotic treatment (Curti et al, 1993) and decrease on Cl efflux induced by mannitol (Teodoro et al, 1998), were showed. In the present investigation, the data indicated a high negative correlation between soil moisture and build up of Na, K and Cl (Table 3).…”
Section: Discussionmentioning
confidence: 71%
“…The perturbation of the transmembrane proton electrochemical gradient must also lead to a defect in intracellular osmolarity, which is consistent with the shape of m210 conidia on plant surface. Plants cell cultures respond to osmotic stress by activating a plasma membrane H + -ATPase-mediated H + -efflux which in turn allows the uptake of more K + in order to compensate for the loss of turgor pressure accompanying cell enlargement (Money and Harold, 1992;Curti et al, 1993;Michelet and Boutry, 1995). On these bases, we thus postulate that reduction in LmPMA1 activity affects the generation of a sufficient intracellular turgor pressure, thus preventing the germination of conidia on host plant surface.…”
Section: Discussionmentioning
confidence: 95%
“…It can be suggested that some complementary factors are necessary for the manifestation of the FC effect. Thus, it was shown that there was a synergism in the stimulating effects of an osmoticum and FC on the proton efflux from the pea internode segments [19], in the Arabidopsis suspension culture [20], as well as during the germination of radish seeds [12]. The above points suggest that osmotic factors, such as high salt concentrations, initiate the manifestation of FC effect; under salt stress, FC affects the ionic balance, and, in particular, increases the ä + / Na + ratio [5].…”
Section: Discussionmentioning
confidence: 97%